Medical marketing in healthcare institutions with public-private partnership mechanisms - А.V. Ivaniuk (Кардіохірургія та інтервенційна кардіологія)
The aim – to reveal the essence of medical marketing in healthcare institutions (HCI) with principles of public-private partnership (PPP). The study used general scientific methods of analysis, synthesis, generalization, interpretation of scientific data, as well as systemic and structural-functional approaches. The article reveals the essence, principles and functions of medical marketing in HCI with the mechanisms of PPP. The substantiation of the main marketing tools is given – business processes and integration processes that contribute to effective marketing in HCI. It also identified the key points that form the structure of medical business processes. The process approach to business process management is disclosed, which allows getting benefits for HCI. The definition and significance of the medical processes integration in HCI on PPP principles is provided, which contributes to the coordination of marketing activities with the strategy development within each integrated complex of HCI and the possibility of obtaining a positive synergistic effect. Examples of internal and external integration are given. The system for managing the external integration process is shown. To stimulate the integration process, bundled payment method has been defined. Conclusions. The article provides justification for medical marketing in HCI with the principles of PPP, focused on business processes and the integration of medical services, which ensures economic, medical and social efficiency and optimal functioning of HCI in market conditions.